Bordetella pertussis infection activates the type I interferon signaling pathway to exacerbate respiratory tract inflammatory response - Wenwen Jiang; Wenwen Jiang; Jiangli Liang; Lukui Cai; Jingyan Li; Qin Gu; Yan Ma; Mingbo Sun; Xin-an Jiao; Li Shi; Li Shi (Frontiers in Immunology)
The upper airway epithelium is the primary site of exposure to Bordetella pertussis and the initiator of host responses to this microbe. B. pertussis may cause serious respiratory infections resulting in major complications, as well as severe impairment of airway function. While pertussis treatment options are limited because the molecular responses in the upper respiratory tract in the early stages of infection have not been characterized. Here, we performed a genome-wide transcriptional analysis of nasal turbinates isolated from mice over 11 days after B. pertussis infection. Using RNA-seq, we characterized the differentially expressed genes and pathways associated with the changes in the nasal turbinates following infection. Statistical analysis revealed that infection is a dynamic process characterized by increased expression of a set of acute inflammatory responses at an early stage. After this initial inflammatory response, we observed increases in the levels of transcripts associated with the regulation of immune processes. In particular, we found that B. pertussis infection significantly increased the levels of type I interferons (IFNs) and related genes in the nasal turbinates at 2 h, 2 days, and 4 days postinfection. Therefore, we investigated the role of type I IFNs in B. pertussis infection in type I IFNs receptor-deficient (IFNAR1−/−) mice. There was no difference in bacterial clearance or adaptive immune responses between wild-type and IFNAR1−/− mice. However, a lack of type I IFNs signaling ameliorated pulmonary immunopathology, reduced the production of inflammatory cytokines and limited the recruitment of neutrophils to the lung during B. pertussis infection. Thus, our findings suggest that inhibiting the effects of type I IFNs may contribute to dampening inflammation, which could be an approach for the treatment of B. pertussis infection and management of the associated disease symptoms.